2006
DOI: 10.1097/01.ajp.0000146218.31780.0b
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Pain-Related Beliefs/Coping Strategies: A Prospective Study

Abstract: Of the 5 personality dimensions studied, only neuroticism was related to the pain-related variables. Multiple hierarchical regression analyses revealed that neuroticism was a significant predictor of residualized change in pain self-efficacy beliefs and pain control appraisals over the time of the study, after controlling for initial values of both constructs. However, the effects were small, suggesting that other factors play a role in the determination of such beliefs, in addition to neuroticism. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 49 publications
2
36
1
1
Order By: Relevance
“…This strategy is adaptive as it tends to confer reduced interference from pain, such that its disuse in FMS patients with higher N may lead to an impaired ability to adjust and adapt to the illness (Jensen, Turner, & Romano, 1992). Contrary to our expectations, we detected no relationship between N and the use of non-effective strategies, such as ''catastrophism'', in contrast to previous FMS studies (Affleck et al, 1992;Asghari & Nicholas, 2006;Jensen, Turner, Romano, & Lawler, 1994;Martínez et al, 2011;Ramírez et al, 2001). However, in healthy controls, N was associated with greater use of ''catastrophizing'', which accords with previous evidence of a relationship between high levels of N and the use of such maladaptive stress-coping strategies in general populations (Bolger, 1990;Gunthert, Cohen, & Armeli, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…This strategy is adaptive as it tends to confer reduced interference from pain, such that its disuse in FMS patients with higher N may lead to an impaired ability to adjust and adapt to the illness (Jensen, Turner, & Romano, 1992). Contrary to our expectations, we detected no relationship between N and the use of non-effective strategies, such as ''catastrophism'', in contrast to previous FMS studies (Affleck et al, 1992;Asghari & Nicholas, 2006;Jensen, Turner, Romano, & Lawler, 1994;Martínez et al, 2011;Ramírez et al, 2001). However, in healthy controls, N was associated with greater use of ''catastrophizing'', which accords with previous evidence of a relationship between high levels of N and the use of such maladaptive stress-coping strategies in general populations (Bolger, 1990;Gunthert, Cohen, & Armeli, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…Asghari and Nicholas (2006), for example, found that those who scored higher on neuroticism were more likely to report higher rates of catastrophizing, anxiety, and passive coping regarding chronic pain. In addition, data show that patients with higher negative affect were associated with higher levels of chronic pain, lower self-efficacy for pain management (PSE), and higher distress (Kersh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Not only do risk and resilience indicators relate to the outcomes of pain and physical functioning in OA patients, but they have also been linked to cognitive-behavioral factors that mediate risk and resilience on pain and physical functioning. Risk factors, such as NA, depression, and neuroticism, have been shown to lead to reduced self-efficacy and physical activity [26-28]. Resilience factors, such as PA, vitality, and extraversion, have been shown to predict increased self-efficacy, physical activity, and more active coping [2, 29-31].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lazarus and Folkman’s model of stress and coping [32], both the primary appraisal of the threat of a stressor, and the secondary appraisal of one’s own resources to cope with a stressor, impact how well one adapts to a chronic illness. Risk factors, such as the ones described herein, impact both primary and secondary appraisal [26-28, 33]. Another perspective that can provide structure to the mechanisms by which risk and resilience relate to pain chronicity and disability is the fear-avoidance model [34].…”
Section: Introductionmentioning
confidence: 99%